Espécies de metazoários parasitos de Acestrorhynchus falcirostris (Cuvier, 1819) (Characiformes: Acestrorhynchidae) de lagos de várzea da Amazônia Central - Dumbo, José Chissiua (Instituto Nacional de Pesquisas da Amazônia - INPA, 2020)
Seventy nine Acestrorhynchus falcirostris were collected from five floodplain lakes of Solimões River: Ananá 15, Araçá 6, Maraçá 6, Preto 13 e Baixio 6 fishes and one of Purus River, São Tomé with 33 fishes. The fishes measured 6-32,5 (22,51±4,5) cm length and 24-318 (117,61±66,5) g weight. Fishes were examined according to the methods applied in the “Laboratory of fish Parasitology - Instituto Nacional de Pesquisa da Amazônia”. Were collected 1.082 parasites of 40 species of six groups. Acestrorhynchus falcirostris is a type host for seven new species and new host of 29 species; one of Monogenoidea: Anacanthorus cinctus; Twelve species of Digenea: Austrodiplostomum compactum; Gonocerca sp.; Phyllodistomum spatula; three species of Rhipidocotyle sp.; three of Prosorhynchoides sp.; Bellumcorpus schubarti; B. major; Bellumcorpus sp.; seven species of Nematoda: Anisakis sp.; Brevimulticaecum sp.; Pseudoproleptus sp.; Guyanema sp.; Travassosnema travassosi paranaensis; Klossinemella iheringi and Porrocaecum sp.; two species of Acantocephala, Quadrigyrus brasiliensis and Q. torquatus; three of Copepoda: Acusicola pellonidis; Miracetyma piraya and Amplexibranchius bryconis; four species of Branchiura: Dolops bidentata; D. geayi; Argulus chicomendesi and A. amazonicus. Digenea was the taxon with the highest species richness, and Nematoda with the highest abundance. Five species A. compactum, Clinostomum marginatum, Procamallanus (Spirocamallanus) inopinatus, Brevimulticaecum sp. and A. pellonidis were secondary species and 35 satellites species. Fifteen satellites species occurred at lake São Tomé showing a little disturbance of this aquatic environment. The intensity of endoparasites (IM=11,83±1,52) was greater than those of the ectoparasites (IM=6,33±1,29). Among endoparasites, A. compactum had highest dominance and among ectoparasites A. pellonidis. The intensity and abundance of larvae (IM=10,56±2,0; AM=8,29±1,02) were significantly higher than those of adults (IM=6,5±1,04; AM=5,38±0,47). The heteroxen species richness was greater than of the monoxen. The species richness was greater in the intestines. The species richness among lakes was similar. The richness, intensity, abundance of larval, adults of endoparasites and ectoparasites were not significantly correlated with standard length. Abundance of Anisakis sp. was positively correlated with standard length. Occupancy of microhabitat and the colonization of lakes were positively correlated with intensity.